Wertpapierprospekte: Markteinführungspublizität nach EU-Prospektverordnung und Wertpapierprospektgesetz 2005 - Kay-Michael Schanz; Christoph Schalast (HfB - Business School of Finance & Management, 2006)
The legal environment for Securities Prospectuses in Germany has changed dramatically with the implementation of the German Securities Prospectus Act (Wertpapierprospektgesetz - WpPG) and the Commission Regulation (EC) No. 809/2004 of 29 April 2004 (Prospectus Regulation) regulating their content and format and harmonizing the requirements for public offerings and stock exchange listings with effect from 1 July 2005. This working report presents the current situation and describes the experience with BaFin, the German Federal Financial Supervisory Agency that now has sole competence for reviewing and approving prospectuses in accordance with the WpPG.
urn:nbn:de:101:1-20080827125
Keywords: K19; K22; 330; IPO; Initial Public Offering; Prospectus; Securities; Stock Exchange Act; Stock Exchange Admission Ordinance; German Financial Supervisory Authority; Prospectus Directive; German Securities Prospectus Act; Wertpapierprospektgesetz; WpPG; Public Offer; Subscription Rights; Employee Incentive Programmes; Stock Exchange; Organised Market; Open Market; Entry Standard; Registration Document; Financial Information; European Passport; Notification; Securities Sales Prospectus Act; Securities Sales Prospectus Ordinance